2020
DOI: 10.1016/j.celrep.2020.107975
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Astrocytic GABA Causes Cortical Hypometabolism and Impedes Functional Recovery after Subcortical Stroke

Abstract: In the originally published version of this article, the author name Jung Moo Lee was spelled incorrectly. This has now been corrected online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 0 publications
4
36
1
Order By: Relevance
“…1d). The increased MCT1 expression in GFAP-positive reactive astrocytes was also observed in an in vivo model of neuroinflammation induced by unilateral adenovirus injection into the motor and somatosensory cortices of the rat brain 8 (Fig. 1g-j).…”
supporting
confidence: 59%
See 1 more Smart Citation
“…1d). The increased MCT1 expression in GFAP-positive reactive astrocytes was also observed in an in vivo model of neuroinflammation induced by unilateral adenovirus injection into the motor and somatosensory cortices of the rat brain 8 (Fig. 1g-j).…”
supporting
confidence: 59%
“…precedes neuronal degeneration or death 1,2 and even directly causes extensive neuronal death [4][5][6] . Recent studies have also reported that reactive astrocytes aberrantly produce GABA to inhibit neighboring neuronal activity and glucose metabolism [7][8][9][10] , which critically contributes to neuronal dysfunction in AD 7,11 . Therefore, in vivo imaging of reactive astrogliosis should have a considerable diagnostic value for the early stages of AD.…”
mentioning
confidence: 99%
“…In the same study, we also found that long-term treatment (> 2 weeks) of selegiline did not show any therapeutic effect, which is due to compensatory up-regulation of astrocytic GABA synthesis (via diamine oxidase) following chronic treatment with an irreversible MAO-B inhibitor, while long-term treatment of reversible MAO-B inhibitor did not turn on this compensatory metabolism (Park et al, 2019). Furthermore, in our recent study a long-term treatment of KDS2010 showed a dramatic effect on post-stroke recovery when it was accompanied by rehabilitation training (Nam et al, 2020). The difference in therapeutic effects in AD between reversible and irreversible MAO-B inhibitors is consistent with current findings in PD.…”
Section: Discussionmentioning
confidence: 77%
“…For example, no difference in dopamine level between MAO-B-deficient mice and wild-type mice (Fornai, Chen, Giorgi, Gesi, Alessandri & Shih, 1999), and no alteration in dopamine level by selegiline treatment (Lamensdorf, Youdim & Finberg, 1996). In addition to these two possibilities, we have reported the critical role of MAO-B in GABA synthesis in reactive astrocytes (Heo et al, 2020;Jo et al, 2014;Nam et al, 2020;Yoon et al, 2014a). Reactive astrocytes produce excess amount of GABA through MAO-B and tonically release GABA to suppress neighboring DA neurons in SNpc, which leads to reduced TH level and DA synthesis, finally causing parkinsonian motor symptoms (Heo et al, 2020).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation